Imunitas dan Produktivitas Puyuh Periode Bertelur dengan Pemberian Tepung Daun Senduduk (Melastoma malabathricum L.) dalam Pakan - Jirfan Dawanto; Niken Ulupi; Hera Maheshwari (Institut Pertanian Bogor, 2024)
Senduduk leaf flour (Melastoma malabatricum L.) is a processed product from weed plants that can potentially be a source of nutrients and bioactive compounds that are beneficial for human and livestock health. This research aims to examine the immunity and productivity of quail during the egg-laying period by administering senduduk leaf flour. This study used 120 female quail aged 40 weeks, which were kept for 4 weeks. The experimental design used was a Completely Randomized Design. The treatment of providing senduduk leaf flour in feed consisted of four treatment levels, namely P0 (without flour), P1 (feed + 1.5% flour), P2 (feed + 3% flour), and P3 (feed + 4.5% flour). The data were analyzed using Analysis of Variance and descriptive analysis. The results showed that adding senduduk leaf meal can reduce egg yolk cholesterol and increase quail immunity. Adding senduduk leaf meal at a 3% level produced the best immunity and performance, with a feed conversion value of 2.81. The 4.5% addition of senduduk leaf flour produced the lowest cholesterol level in quail egg yolk. Keywords: egg quality, immunity, performance, quail, senduduk leaf